A c-di-GMP-Based Switch Controls Local Heterogeneity of Extracellular Matrix Synthesis which Is Crucial for Integrity and Morphogenesis of Escherichia coli Macrocolony Biofilms. Issue 23 (22nd November 2019) - Serra, Diego O.; Hengge, Regine
Abstract: The extracellular matrix in macrocolony biofilms of Escherichia coli is arranged in a complex large-scale architecture, with homogenic matrix production close to the surface, whereas zones further below display pronounced local heterogeneity of matrix production, which results in distinct three-dimensional architectural structures. Combining genetics, cryosectioning and fluorescence microscopy of macrocolony biofilms, we demonstrate here in situ that this local matrix heterogeneity is generated by a c-di-GMP-dependent molecular switch characterized by several nested positive and negative feedback loops. In this switch, the trigger phosphodiesterase PdeR is the key component for establishing local heterogeneity in the activation of the transcription factor MlrA, which in turn activates expression of the major matrix regulator CsgD. Upon its release of direct inhibition by PdeR, the second switch component, the diguanylate cyclase DgcM, activates MlrA by direct interaction. Antagonistically acting PdeH and DgcE provide for a PdeR-sensed c-di-GMP input into this switch and—via their spatially differentially controlled expression—generate the long-range vertical asymmetry of the matrix architecture. Using flow cytometry, we show heterogeneity of CsgD expression to also occur in spatially unstructured planktonic cultures, where it is controlled by the same c-di-GMP circuitry as in macrocolony biofilms. Quantification by flow cytometry also showed CsgD ON subpopulations with distinct CsgD expression levels and revealed an additional fine-tuning feedback within the PdeR/DgcM-mediated switch that depends on c-di-GMP synthesis by DgcM. Finally, local heterogeneity of matrix production was found to be crucial for the tissue-like elasticity that allows for large-scale wrinkling and folding of macrocolony biofilms. Graphical Abstract: Unlabelled Image Highlights: Local matrix heterogeneity in E. coli macrocolony biofilms is controlled by a c-di-GMP-dependent molecular switch. In this switch, the trigger phosphodiesterase PdeR is the key component for establishing local heterogeneity in the expression of the matrix regulator CsgD. The second switch component, the diguanylate cyclase DgcM, directly activates MlrA-mediated csgD transcription and—via its c-di-GMP synthesis—operates a novel fine-tuning feedback. Antagonistically acting PdeH and DgcE provide for c-di-GMP input into this switch and—via their spatially differentially controlled expression—generate the long-range vertical asymmetry of the matrix architecture. Local heterogeneity of matrix production is crucial for tissue-like elasticity required for E. coli macrocolony biofilm integrity during large-scale wrinkling and folding.